Hippocampal sclerosis and status epilepticus: cause or consequence? A MRI study - Kuster,Gustavo Wruck (2007)
BACKGROUND: Transient imaging abnormalities, including changes on diffusion-weighted imaging (DWI), may be seen in status epilepticus. These abnormalities can be followed by hippocampal sclerosis. CASE REPORT: We report a 15-year-old lady with focal non convulsive status epilepticus (NCSE) and focal slowing on EEG. DWI exhibited abnormal hyperintense signals in bilateral temporal and insular cortices. After 3 weeks, MRI performed a localizated hippocampal atrophy. CONCLUSION: The MRI findings indicated vasogenic and cytotoxic edema during seizure activity and subsequent loss of brain parenchyma.